Ensayos de propagación de algunas especies forestales aptas para el manejo de la microcuenca La Lejía, Cundinamarca, Colombia - Pérez-Vega, Julieth; Acosta Rodríguez, Leidy; Parrado-Rosselli, Ángela (Revista Científica, 2012)
Propagation trials were conducted on 13 tree species considered in previous studies as a suitable for rehabilitation of the La Lejiamicrobasin in Cundinamarca, Colombia. Studied species were Guadua angustifolia (guadua), Trichanthera gigantea (madre de agua), Tabebuia rosea (ocobo), Cordiaalliodora (nogal cafetero), Croton spp (drago), Erythrina edulis (balú), Persea americana (aguacate), Cedrela montana (cedro de altura), Cedrela odorata (cedro rosado), Ficus spp (caucho), Ficuscarica (brevo), Psidium guajava (guayaba) and Solanum betaceum (tomate de árbol). In three community nurseries we evaluated the response of seeds, rescued seedlings and hardwood cuttings in five substrate types (i.e. 1. soil, 2. soil and organic fertilizer, 3. soil and rice husk, 4. soil and a microbial mixture, and 5. all types combined). Species response was measured during three months in terms of germination/survival percentage and changes in leaf number and seedling height. The results showed that survival and growth were significantly higher in soil and organic fertilizer and soil and rice husk for any propagation type. The best performance was exhibited by Cedrela Montana and Erythrinaedulis. We highlight the importance of community nurseries for successful monitoring and implementation of propagation strategies of valuable tree species for local communities.